Ahl Al-Kitab and Politic Context in Indonesia - Mujiburrahman Mujiburrahman (Universitas Islam Negeri Alauddin Makassar, 2015)
This article presents about the concept of “ahl al kitab” on the context of political aspect in Indonesia. It aims to to show the existence of ‘ahl kitab’ in relation to the political aspect in Indonesia. The methodology applied was using normative approaches in order to be able to find out the extent of ‘Ahl al-Kitab’ on the context of political aspect in Indonesia. It is shown that Islam supports the existence of the other religions. The prophet Muhammad stated that Islam is a continuity of previous religions. Furthermore the discourse of ‘ahl al Kitab’ on political aspect in Indonesia is related to the existence of this statement as a position in between secular and Islamic nation. It is realized that the extent of ‘‘ahl al Kitab’ concept that covers all of religions in Indonesia still arises problem concerning the existence of religions and believe that schools are involved in educating about religion field of study. In fact, the Moslem scholars in Indonesia attempt to extent the concept of ‘ahl al Kitab’ so that the existence of the other religions is accepted as officially recognized religions, including inter-faith marriage matters.